ENHANCING WORKFORCE COMPETITIVENESS THROUGH IMPROVING QUALITY OF EDUCATION – AN INDISPENSABLE MEANS FOR OVERCOMING POVERTY (International Journal of Innovative Technologies in Economy, 2018)
Increasing globalisation and integration of economies entailed the rise of global problems as well. Today, the greater part of the planet is starving. The problems are aggravated by the advancement of scientific and technological progress which leaves the colossal part of human workforce beyond production process. It is impossible to overcome poverty without economic growth. However, economic growth does not affect poverty similarly in all countries. 1 % growth of GDP reduces income poverty by 1 % minimum and 4 % maximum depending on the number of jobs created. It is possible to have economic growth in a country without creating a substantial number of jobs. Among many instruments of improving employment indicators and overcoming poverty we consider education to be the most crucial.